Investigation of the thermo-mechanical properties of hot stamping steels - Merklein, Marion; Lechler, Jürgen (Tagungsband Metal Forming Conference 2006, Birmingham, England, 2006)
Within the innovative hot forming process for sheet metals, called hot stamping, it is possible to combine forming and quenching in one process step. This affords the opportunity to manufacture components with complex geometric shapes, high strength and a minimum of springback which currently find applications as crash relevant components in the automotive industry. As standard material for hot stamping the quenchenable high strength steel 22MnB5 is commonly used. With regard to the numerical modeling of the process, the knowledge of thermal and thermo-mechanical properties of the material is required. To determine the thermo-mechanical material characteristics, the flow behavior of the steel 22MnB5 in the austenitic state has been investigated by conductive, hot tensile tests with a Gleeble 1500 system dependent on the time-temperature characteristic of the hot stamping process. © 2006 Elsevier B.V. All rights reserved.
LFT Import::2019-08-05 (1269)
Keywords: 22mnB5; Flow behavior; High strength steels; Hot stamping; Thermo-mechanical properties